2000
DOI: 10.1097/00002030-200012220-00006
|View full text |Cite
|
Sign up to set email alerts
|

Cell-associated HIV-1-DNA quantitation after highly active antiretroviral therapy-treated primary infection in patients with persistently undetectable plasma HIV-1 RNA

Abstract: In this highly selected population of patients with excellent plasma virological response under HAART, HIV-1 DNA showed a progressive decrease but was still detectable in 92.3% of samples at month 18, whereas all LNMC samples tested scored positive for HIV-1 DNA. The utility of proviral HIV-1-DNA monitoring was not clearly demonstrated in this 18-month follow-up of HAART-treated primary-infected patients. However, this finding could be reconsidered when using other therapeutic strategies such as structured tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 21 publications
3
20
0
1
Order By: Relevance
“…The high levels of tat mRNA observed with the ART-treated HIV-2 cohort suggested that the therapeutic regimens used were unable to reduce the rate of de novo cell infection. These data contrast with those for ART-treated HIV-1 ϩ patients, in which virological response is usually associated with a sharp decline in MS mRNA (4,21,62) and in the proportion of MS mRNA relative to US mRNA in PBMC (57), as well as with a progressive decrease in proviral DNA (23,58,59) despite the low-level viremia that can frequently be detected using ultrasensitive assays (17,43).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The high levels of tat mRNA observed with the ART-treated HIV-2 cohort suggested that the therapeutic regimens used were unable to reduce the rate of de novo cell infection. These data contrast with those for ART-treated HIV-1 ϩ patients, in which virological response is usually associated with a sharp decline in MS mRNA (4,21,62) and in the proportion of MS mRNA relative to US mRNA in PBMC (57), as well as with a progressive decrease in proviral DNA (23,58,59) despite the low-level viremia that can frequently be detected using ultrasensitive assays (17,43).…”
Section: Discussionmentioning
confidence: 63%
“…Viremia levels were similar in the treated and untreated HIV-2 cohorts, due to the low-level viremia detected in some of the ART-treated HIV-2 ϩ patients ( Table 2). Of note, in contrast with the progressive decline in proviral DNA levels usually observed with ART-treated HIV-1 ϩ patients (23,58), proviral DNA did not significantly differ between untreated and treated HIV-2 ϩ patients (Fig. 3A), despite the prolonged treatment.…”
Section: Relationship Of Plasma and Cell-associated Viral Load With Cmentioning
confidence: 72%
“…replication among individuals with plasma HIV-1 RNA below the limits of detection. Data from others' studies similarly suggest that PBMC HIV-1 DNA loads correlate with markers of viral nucleic acid synthesis (2,4,20,27,37,61), as have intracellular viral RNA levels (4) and the ratio of unspliced to multiply spliced HIV-1 mRNA (19). Decreases in total HIV-1 levels associated with viral replication well-suppressed by HAART appear primarily due to decreases in unintegrated HIV-1 DNA (27).…”
Section: Discussionmentioning
confidence: 91%
“…The amount of HCV RNA in each biopsy was quantified by RT-PCR using the Amplicor HCV Monitor 1.0 assay (Roche Diagnostic Systems, Branchburg, NJ; 25). The technique was adapted from the Agence Nationale de Recherche sur le SIDA method used for HIV RNA quantitation in lymph nodes (26). Briefly, 100 l of the proteinase K-digested specimens were mixed with 400 l of Monitor lysis buffer containing guanidine thiocyanate with addition of the Roche-supplied internal quantitative standard (IQS) required for determining RNA levels.…”
Section: Hcv Rna Quantitation In Frozen Liver Tissuesmentioning
confidence: 99%